The Role of Corporate Culture in Maintaining Organizational Operations during the Global Financial Crisis - Sabri, Hala Abdulqader (Journal of Social and Development Sciences, 2013)
The global financial crisis that unfolded in 2008 presents leaders and managers with many challenges. Yet, the lessons of this crisis also present opportunities to create more responsive and flexible organizations capable of overcoming the risks and troubles more effectively. However, in the midst of this crisis it is apparent that most of the attention seems to be devoted to changing regulatory structures and rules that affect corporate governance and the financial markets. This paper argues that the root causes of such crisis are deep and unlikely to be addressed through public policy or external means alone. Most of the problems during this financial crisis can be traced to that most CEOs and executives did not actually pay attention to their company’s culture as they did with regard to their profits, assets, brands, and quality of products and services. The paper then explores the vulnerability of firms whose executives fail to manage their company’s culture at the time of crisis with as much thoroughness as they apply to managing their financial, operational or technology risks. Finally, the paper lays out a leadership and management strategy based on the strengths of maintaining a strong corporate culture guided by adherence to the core values of the organization.